Partai Politik Lokal Dan Evaluasi Dalam Penyelenggaraan Dana Otonomi Khusus Aceh - Silkika Nurparijah (Universitas Islam Indonesia, 2022)
Aceh as a special autonomous region can regulate and manage its own region. This authority is given by the central government through decentralization and deconcentration which is regulated in Law Number 23 of 2014 concerning Regional Government. As a special autonomous region, Aceh is given the freedom to establish political parties and manage Dana Otonomi Khusus (DOKA) (the Aceh Special Autonomy Fund) for the welfare of the Acehnese people, but Aceh is still ranked first as the poorest region at the Sumatera level, data obtained through the Central Statistics Agency (BPS). This research method uses normative research to examine and analyze local government policies on the Aceh Special Autonomy Fund (DOKA) with a conceptual approach. The results of this The results of this study conclude from the corruption case in Aceh and the first poverty, First that local political parties are the sectoral leaders of Aceh's special autonomy funds through legislative and executive seats in the Aceh region, special autonomy funds are misused through regional infrastructure development. Second, that the special autonomy funds are controlled by combatants of the Gerakan Aceh Merdeka (GAM) Free Aceh Movement through the collection of nangroe taxes which are deposited to the top officials of the Free Aceh Movement from funds for regional development planning and implementation.Key Words: Implementation of the Special Autonomy Fund for Aceh (DOKA), Aceh local political parties and the Free Aceh Movement (GAM) AbstrakAceh as a special autonomous region is allowed to regulate and manage itself. This authority is given by the central government through the mechanism of decentralization and deconcentration as regulated in Law Number 23 of 2014 on Regional Government jo. Law Number 11 of 2006 on the Government of Aceh. As a special autonomous region, Aceh is given the freedom to establish local political parties and to manage the Aceh Special Autonomy Fund (DOKA) for the welfare of the Acehnese people, yet Aceh is still ranked as the poorest region in Sumatra level based on data obtained through the Central Statistics Agency (BPS). This research method uses normative research to examine and analyze local government policies on the Aceh Special Autonomy Fund (DOKA) with a conceptual approach. The results of this study conclude from the corruption case in Aceh and the first poverty data, that local political parties as the leading sector of Aceh's special autonomy funds through the legislative and executive seats in the Aceh region, special autonomy funds are misused through regional infrastructure development. Second, that the special autonomy funds are controlled by combatants of the Free Aceh Movement (GAM) through Nanggroe tax collection which is deposited with the top officials of the Free Aceh Movement from funds for regional development planning and implementation. Kata-kata Kunci: Penyelenggaraan Dana Otonomi Khusus Aceh (DOKA); Partai Politik Lokal Aceh dan Gerakan Aceh Merdeka (GAM)